Resting-State Functional Connectivity Predicts Cognitive Impairment Related to Alzheimer's Disease - Lin, Qi; Rosenberg, Monica D.; Yoo, Kwangsun; Hsu, Tiffany W.; O'Connell, Thomas P.; Chun, Marvin M. (Frontiers in Aging Neuroscience, 2018)
Resting-state functional connectivity (rs-FC) is a promising neuromarker for cognitive decline in aging population, based on its ability to reveal functional differences associated with cognitive impairment across individuals, and because rs-fMRI may be less taxing for participants than task-based fMRI or neuropsychological tests. Here, we employ an approach that uses rs-FC to predict the Alzheimer’s Disease Assessment Scale (11 items; ADAS11) scores, which measure a range of cognitive abilities, in novel individuals. We applied this technique, connectome-based predictive modeling, to a heterogeneous sample of 59 subjects from the Alzheimer’s Disease Neuroimaging Initiative, including normal aging, mild cognitive impairment, and AD subjects. First, we built linear regression models to predict ADAS11 scores from rs-FC measured with Pearson’s r correlation. The positive network model tested with leave-one-out cross validation (LOOCV) significantly predicted individual differences in cognitive function from rs-FC. In a second analysis, we considered other functional connectivity features, accordance and discordance, which disentangle the correlation and anticorrelation components of activity timecourses between brain areas. Using partial least square regression and LOOCV, we again built models to successfully predict ADAS11 scores in novel individuals. Our study provides promising evidence that rs-FC can reveal AD-related cognitive impairment in an aging population, although more development is needed for clinical application.